The Association of Pain with Walking Speed and Functional Abilities in Patients Suffering from Progressive forms of Multiple Sclerosis - Mitrovic, Sindi (Medical Research, 2024)
Introduction/Aim: In progressive forms of MS, the frequency of pain increases as the disease progresses affecting patients’ functional abilities and making the disease much more complex. We conducted a cross-sectional study to examine the association of pain with walking speed and functional abilities in patients who suffer from progressive forms of multiple sclerosis. Material and methods: The cross-sectional study was conducted at the Clinic for rehabilitation ˮDr Miroslav Zotovićˮ in the period from January 2020 to September 2022. The research included 35 patients with PPMS and SPMS admitted to this clinic for rehabilitation. Demographic and socio-epidemiological data and disease-related data were collected. Pain intensity was assessed using Numeric Rating Scale (NRS) and the subscale related to Pain/Discomfort (Pain/Discomfort, P/D). Subjective perception of gait impairment was assessed by a subscale related to walk (WL – Walk). Walking speed was measured by The Timed 25 Foot Walk (T25FW). Results: There is a significant strong correlation between WL and P/D (rho=0.773; p
Keywords: Key words: pain, walking speed, functional disability, progressive forms of multiple sclerosis